PENGARUH PUPUK KANDANG AYAM DAN BOKASHI KULIT PISANG TERHADAP KADAR AIR TANAH DAN C-ORGANIK SERTA PERTUMBUHAN JAGUNG PADA REGOSOL PESISIR NAMBO - HAPSA, SITTI; REMBON, FRANSISCUS S.; LEOMO, SITTI (Jurnal Agroteknos, 2023)
This study aims to determine the dose of chicken manure and banana peel bokashi kepok which has a better effect on increasing soil moisture content and organic C content in Regosol soil and corn plant growth, and to determine the effect of adding chicken manure and kepok banana peel bokashi on the growth of maize. This research was conducted at the Field Experimental Garden II, Faculty of Agriculture, Halu Oleo University and soil sampling was carried out on the coast of Nambo. Soil sample analysis was carried out at the soil test laboratory of the Department of Soil Science and the Integrated Laboratory of Halu Oleo University, which took place from April to June 2022. The design used was a factorial randomized block design with two factors, namely chicken manure and kepok banana peel bokashi. The results showed that the application of chicken manure and kepok banana peel bokashi has a significant effect at p< 0,05 and p